Effectively Navigating Leadership Transitions in a Higher Education Context - Kevin Gushiken; Hal Pettegrew; Richard Rhoads (Journal of Scholarly Engagement, 2020)
Leadership transition in higher education is inevitable and critically important. This article seeks to describe a successful leadership transition that has occurred in a doctoral program director position of a religious graduate school, written by the outgoing director, the incoming director, and the director of the department in which this transition took place. Considerations of a leadership transition as articulated in the literature are examined. The authors offer key principles and recommendations for higher education institutions approaching or undergoing a leadership change with the aim to encourage a smooth and stable transition. Keywords: leadership transition, succession plan, higher education, faculty, leadership, religious institutions, Christian colleges